Organologi Pembuatan Calempong Kayu oleh Fatimah di Desa Lipatkain Utara Kecamatan Kampar Kiri Kabupaten Kampar Provinsi Riau - Reksi Saputra; Tengku Ritawati (Jurnal Syntax Admiration, 2024)
This research is based on the researcher's desire to describe the organology of making Calempong wood by Fatimah in the village of North Lipatkain, Kampar Kiri District, Kampar Regency, Riau Province. In ancient times, according to Fatimah's story, this wooden Calempong was used by people who were in the fields, when they felt bored because there was nothing to play with, Calempong was made from cikubuang wood which was arranged on piaku and was called Wooden Calempong which was used for self-entertainment and media for learning Calempong. This research uses Andre Schaeffner's theory (2015: 167) which looks at the organological aspects of 1) Inventory, 2) Terminology/naming, 3) Classification of musical instruments, 4) Description of musical instrument construction, 5) Sound production, 6) History of musical instruments, 7) Status of craftsmen, 8) Function of musical instruments, 9) Socio-cultural factors, 10) Study of symbolism and aesthetic aspects of musical instruments. Descriptive analysis research method using qualitative data. The data obtained was processed using data analysis techniques through procedures for searching and compiling the results of observations, interviews and documentation carried out systematically. The resource person is Fatimah, a Calempong wood craftsman and traditional artist who is often invited to events in the folding village. The results of the research show that the wooden Calempong has 5 tones and the tones have a different pitch arrangement, namely 1,3,4,2,5, which means that the notes in the wooden Calempong cannot be said to be in the diatonic scale. With a shape somewhat similar to an elongated triangle, with the aim of beautifying the shape of the blades, they are arranged on top of the Piaku and then played by hitting each blade using a panggugua.